Everything Loose: Ron Athey’s Acephalous Monster at REDCAT - Ventzislavov, Rossen (Aesthetic Investigations, 2021)
The work of artist Ron Athey has long befuddled the art historical establishment and has mostly remained under the philosophical radar. In this review of Athey’s Acephalous Monster, performed on August 28, 2021, at the Roy and Edna Disney/CalArts Theater in Los Angeles, I propose a philosophical frame- work for Athey’s radical reinvention of ethical categories like agency, mutuality and communion. I describe the performance and its critical context in order to tease out the aesthetic dimension of this reinvention and the subversive power of reconstituting personhood along lines of collective artistic jubilation and creative survival.